Efficient transition from partial nitritation to partial nitritation/Anammox in a membrane bioreactor with activated sludge as the sole seed source. (August 2020) - Huang, Xiaowu; Mi, Wenkui; Hong, Nian; Ito, Hiroaki; Kawagoshi, Yasunori
Abstract: A lab-scale membrane bioreactor (MBR) was employed to carry out the partial nitritation/Anammox (PN/A) process from conventional activated sludge. Seed sludge was cultivated under microaerobic conditions for 10 days before seeding into the MBR. The bacterial community was analyzed on the basis of cloning and sequencing of 16S rRNA gene. Relative slow ammonia oxidation rates (3.2–13.0 mgN/L/d) were established in the microaerobic cultivation period. In the continuous MBR operation, the nitritation was achieved in the first 16 days and the reactor produced a balanced ratio between ammonia and nitrite which favored the proliferation of Anammox bacteria. Efficient transition from PN to PN/A was achieved in two months which was supported by appearance of reddish spots on the reactor inner wall and the concurrent consumption of ammonium and nitrite. The PN/A performed a robust and high-rate nitrogen removal capability and achieved a peak nitrogen removal of 1.81 kg N/m 3 /d. 16S rRNA gene-based analysis indicated that " Nitrosomonas sp." and " Candidatus Jettenia sp." accounted for ammonia oxidation and nitrogen depletion, respectively. Denitratisoma facilitated denitrification in the reactor. The present study suggested that a pre-cultivation of seed sludge under microaerobic conditions assists fast realization of PN and further convoyed efficient transition from PN to PN/A. Knowledge gleaned from this study is of significance to initiation, operation, and control of MBR-PN/As. Highlights: Efficient transition from PN to PN/A was achieved in an MBR in two months. Microaerobic cultivation of seed sludge facilitated fast realization of PN and PN/A. Reddish dots on the reactor wall could be noted as an indicator of Anammox reaction. Biofilm-based PN/A process is sustainable under over 1.0 mg DO/L. MBR was an efficient tool to initiate PN/A from CAS.